Groundwater pollution - Bharti, Pawan Kr. (New Delhi : Biotech Books, 2012)
Study conducted at Binjhole Village, Panipat, India.
Includes bibliographical references (p. [219]-236) and index.
Keywords: Groundwater -- Pollution -- India -- Binjhole; Textile industry -- Environmental aspects -- India -- Binjhole; Groundwater